Study of using some microalgae in treatment of domestic wastewater - Muhanad H. S. Al-Jubori; Jihad D. M. Al-Janabi; Youssef J. I. AI-Shahrii (Tikrit Journal of Pure Science)
The present study includes growing five species of microalgae which are Chlorella sacchrophila, Chlorella vulgaris, Scendesmus obliquus, Botryococcus braunii, Chlamydomonas reinhardtii algae and using of biological treatment of domestic wastewater. The present study shows that the studied microalgae has ability to reduce the pollutants average in domestic wastewater for all stations. As the results show that the highest percentage of removal in electrical conductivity (31%) register in case using C. vulgaris, while the lowest percentage (5%) register when using C. sacchrophila. The used algae variant in their ability to reduce Salinity value which reaches the highest percentage of reduce for salinity values (21%) when using C. vulgaris and the lowest percentage of reduce was ( 6%) register when using C. sacchrophila .